Asciminib for Philadelphia chromosome positive leukemias - Timothy P. Hughes; Deborah L. White; David T. Yeung (Haematologica, 2025)
Twenty-five years after the introduction of imatinib, we have entered a new era of therapy for Chronic Myeloid Leukemia (CML). Despite the development of second and third generation (2G and 3G) tyrosine kinase inhibitors (TKIs), their impact have been incremental in improving outcomes for CML patients. While frontline use of 2G TKIs have improved molecular response rates and reduced progression to blast phase, there has been no improvement in overall survival compared to imatinib, likely due to the higher toxicity and consequent higher non CML-related mortality. Imatinib remains the most prescribed therapy for CML worldwide, despite it being the least potent TKI and most prone to resistance and progression. Asciminib, the first STAMP (Specifically Targeting the ABL Myristoyl Pocket) inhibitor, binds to the myristoyl pocket of BCR::ABL1. Its specificity minimises off-target toxicity which enables asciminib to finally break this frustrating link between potency and toxicity. After a decade of clinical trials, both in patients with resistance and intolerance to two or more TKIs, and more recently in the frontline setting, asciminib is fulfilling its early promise of a more rapid and reliable pathway to long-term disease control with minimal toxicity. There are however some unexpected challenges when using asciminib that require further investigation. In this Spotlight we review the key studies and outline the potential impact and current limitations of this first STAMP inhibitor in the CML setting and in other leukemias where ABL1 or ABL2 is the key target.